A Culture of Uncertainty: Interaction and Organizational Memory in Software Engineering Teams under a Productivity Scheme. Issue 6 (June 2017) - Kameo, Nahoko
Drawing on an ethnography of software engineering teams that introduced a new and empowerment-centered productivity scheme, this study delineates how, despite management's affirmation of its commitment, software engineers produced and reproduced a 'culture of uncertainty' characterized by constant doubt about how long the scheme would last. Engineers shared previous experiences of failed productivity schemes and collectively used this organizational memory to understand their new situation. Workers drew on this organizational memory in everyday interaction to sustain a culture in which everyday management decisions served as indicators of management's potential abandonment of the scheme; as a result, workers remained uncommitted to the scheme. Workers interactionally employed organizational memory as a resource that they used to interpret and respond to changes. Analysis of this process shows the links between organizational memory, culture creation, and culture's influence on productivity scheme changes.